Uma investigação das relações familiares na peça 'Do Fundo do Lago Escuro (Assunto de Família)', de Domingos de Oliveira - Massadar, Claudia Toledo (1983)
Our dissertation deals with three different, concepts of the family relationships: pseudo-mutuality, developed by Lyman Wynne in the United States, Jacques Hochmann's fusion postulate, from France and mystification, developed by Ronald Laing in Eng1and, which are applied to the fami1y structure of a contemporary Brazilian theatre play, Domingos de Oliveira's 'Do Fundo do Lago Escuro'. The above-mentioned concepts are basic in order to understand the dynamics of family relationships within a systemic (non-psychoanalytic) point view. They were chosen due to their similarities and a1so to the fact that all three are the outcome of intensive studies of families, with a schizophrenic member, in three different countries. We tried to establish a comparison among these concepts in terms of their simi1arities, their methodologica1, theoretical and ideological differences and their complementary aspects, and to test their applicability to a family Structure representative of a certain stratum of Brazilian society in a given historical moment. Our main conclusion is that the three concepts examined: pseudo-mutuality, fusion postulate and mystification, can be applied, with some degree of success, to a certain type of Brazilian family structure, as well as to a family group where no member displays a manifest schizophrenic syndrome.